2006
DOI: 10.1016/j.soildyn.2006.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface attenuation modelling based on rock shear-wave velocity profile

Abstract: In a previous study published in this journal, the authors developed a comprehensive methodology for modelling the shear wave velocity profile in crustal rock, for purposes of seismic hazard assessment. The derived shear wave velocity profile was used to estimate the amplification and attenuation mechanisms in the transmission of seismic waves. The ability to conduct seismic hazard assessments in regions of low and moderate seismicity is greatly enhanced by this new modelling approach, given that developing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 26 publications
7
64
0
Order By: Relevance
“…We do not address what the median value of κ 0 and its uncertainty should be for the carbonate platform regions of CENA, which are common in the Midwest region of North America. One might expect site attenuation in this region to be greater than that for hard rock (e.g., Chandler et al, 2006). Figure 21 shows mean values of hard-rock κ 0 in CENA from various sources in the literature, which range from 0.002 to 0.009 s (Atkinson, 1984(Atkinson, , 1996Toro and McGuire, 1987;Silva et al, 1988;Silva and Darragh, 1995;Chapman et al, 2003;Atkinson and Boore, 2006;Campbell, 2009).…”
Section: Reference Rock Unit Weightmentioning
confidence: 98%
“…We do not address what the median value of κ 0 and its uncertainty should be for the carbonate platform regions of CENA, which are common in the Midwest region of North America. One might expect site attenuation in this region to be greater than that for hard rock (e.g., Chandler et al, 2006). Figure 21 shows mean values of hard-rock κ 0 in CENA from various sources in the literature, which range from 0.002 to 0.009 s (Atkinson, 1984(Atkinson, , 1996Toro and McGuire, 1987;Silva et al, 1988;Silva and Darragh, 1995;Chapman et al, 2003;Atkinson and Boore, 2006;Campbell, 2009).…”
Section: Reference Rock Unit Weightmentioning
confidence: 98%
“…Atkinson (1996) observed this for hard rock sites in eastern and western Canada. Chandler et al (2006), who used a global dataset to derive their correlations, admit their scatter is partly due to the variability of the underlying crustal Q and V S profile for similar V S30 values. 2.…”
Section: κ: a Multitude Of Applications Physical Interpretations Anmentioning
confidence: 99%
“…Edwards et al (2011) compared the classic method with their broadband inversion, and compared the classic with the transfer-function approach, both finding similar results, but with considerable scatter. Chandler et al (2006) compared the classic method to that of response spectral fitting and found the latter approach overpredicted κ 0 values. Biasi and Anderson (2007) found that the displacement-based method gives an upper bound with respect to the classic method.…”
Section: κ: a Multitude Of Applications Physical Interpretations Anmentioning
confidence: 99%
“…For the downhole rock (assuming it is equivalent to rock outcrop with V S30 1000 m=s), the following predictions can be made for the median value: κ 0 0:026 s according to the global database of Chandler et al (2006), 0.022 s according to Silva et al (1998), who worked with California data, 0.021 s according to Van Houtte et al (2011), 0.017 or 0.020 s according to the two correlations of Edwards et al (2011), based on Swiss data, and 0.018 s according to Drouet et al (2010), who worked with French data. Taking into account their variation, the predictions are in reasonable agreement with our downhole results.…”
Section: Comparisons With Literaturementioning
confidence: 99%